Pelatihan Keterampilan Sosial Dan Peran Guru Dalam Membangun Lingkungan Bebas Perundungan - Putri, Gusti Ayu Made Arna; Noviantari, Putu Suarniti; Payadnya, I Putu Ade Andre; Suwija, I Ketut; Diva, I Komang Budiarta (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
This Community Service program aims to enhance social skills and raise awareness of the importance of creating a safe, inclusive, and bullying-free school environment through training for teachers and students in grades 2–6 at SD Negeri 3 Celuk. The activity was carried out on July 10, 2025, using an educational approach tailored to the developmental stages of the participants, ensuring that the material was easily understood and applicable to their daily behavior. The training was conducted interactively through lectures, group discussions, role-play simulations, and the signing of written commitments by students to refrain from bullying as a form of support toward a positive school culture. For teachers, the program focused on strategies to manage a supportive classroom climate, strengthen communication skills, and implement early intervention techniques when signs of bullying appear, enabling them to improve both prevention and handling of bullying incidents. To evaluate the effectiveness of the program, pretests and posttests were administered to teachers. The results showed a significant increase in understanding, particularly among teachers, with the average score rising from 72% before the training to 93% afterward. This improvement indicates that the training contributed to enhanced knowledge, increased empathy, and better social skills that support the realization of a child-friendly school. In addition to providing direct benefits to the community of SD Negeri 3 Celuk, this program is expected to serve as a good practice model that can be replicated in other elementary schools, thereby strengthening sustainable efforts to prevent bullying within primary education settings.